Work-Life Balance Challenges of Indigenous Health Management Employees in the Medical Tourism Sector of Kerala, India (Journal of Business Management and Accounting, 2011)
In contrast to the large-scale multinational projects, medical tourism sector in Kerala mainly constitutes indigenous health management practices coupled with local tourism industry.  The  government  and  bureaucracy  project  medical  tourism  as  an  engine  of  economic  growth.  It  is  considered  as  an  excellent  source  of  foreign  exchange  and  employment generation to revive the local economy. As it mainly involves indigenous methods   and   techniques   of   health   care   management,   further   development   and   sustainability  of  this  sector  fully  depends  on  highly  committed,  skilled  and  qualifi ed manpower.  However,  no  detailed  studies  regarding  the  potential  problems  faced  by  the human resource capital in this sector are available.  This paper is an attempt to analyze  the  various  challenges  associated  with  the  work-life  balance  (WLB)  of  the  employees working in the indigenous health care management practices linked to the medical tourism industry of Kerala, India.  Data for the study were collected from 157 individuals, working in the medical tourism sector spanning around 24 organizations. The results indicated the positive and negative associations of the various challenges with the WLB of the employees.